Decline of the Steller sea lion in Alaskan waters : untangling food webs and fishing nets (National Academies Press, 2003)
For an unknown reason, the Steller sea lion population in Alaska has declined by 80% over the past three decades. In 2001, the National Research Council began a study to assess the many hypotheses proposed to explain the sea lion decline including insufficient food due to fishing or the late 1970s climate/regime shift, a disease epidemic, pollution, illegal shooting, subsistence harvest, and predation by killer whales or sharks. The report's analysis indicates that the population decline cannot be explained only by a decreased availability of food; hence other factors, such as predation and illegal shooting, deserve further study. The report recommends a management strategy that could help determine the impact of fisheries on sea lion survival -- establishing open and closed fishing areas around sea lion rookeries. This strategy would allow researchers to study sea lions in relatively controlled, contrasting environments. Experimental area closures will help fill some short-term data gaps, but long-term monitoring will be required to understand why sea lions are at a fraction of their former abundance.